INTERNALISASI PLURALISME AGAMA DALAM PEMBELAJARAN SOSIAL DAN EMOSIONAL - Willy Ramadan; Ali Mustofa (Nizham Journal of Islamic Studies, 2022)
Based on the results of the thinking of researchers who consider the importance of social and emotional knowledge framed with pluralism to develop the competence of students as social beings in schools. This research provides a conduction to the internalization of pluralism through culture that can be a source of positive support for individuals. This is especially true for minority and immigrant groups in pluralist societies where houses of worship can be homes of community and identity, especially when the dominant group suppresses public expression and acceptance of group norms and values.